Shortcut learning leads to sex bias in deep learning models for photoacoustic tomography - Knopp, Marcel; Bender, Christoph J.; Holzwarth, Niklas; Li, Yi; Kempf, Julius; Caranovic, Milenko; Knieling, Ferdinand; Lang, Werner; Rother, Ulrich; Seitel, Alexander; Maier-Hein, Lena; Dreher, Kris (International journal of computer assisted radiology and surgery, 2025)
Shortcut learning has been identified as a source of algorithmic unfairness in medical imaging artificial intelligence (AI), but its impact on photoacoustic tomography (PAT), particularly concerning sex bias, remains underexplored. This study investigates this issue using peripheral artery disease (PAD) diagnosis as a specific clinical application.